2022
DOI: 10.46481/jnsps.2022.252
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Evaluation and Minerals Phases Identification of Fine and Coarse Okelele Block Clay Composites for Furnace Lining Application

Abstract: The suitability of fine and coarse Okelele clays as refractory raw materials for furnace lining application was investigated. The clay samples were crushed and pounded with a mortar and pestle to a particle size of 20 microns. 230 g each of fine clay was mixed with 50 mls of water inside a bowl and stirred thoroughly to form homogenous plastic paste. 10 g, 15 g, 25 g, 35 g and 45 g of coarse clay were added respectively to the 230 g of homogenous fine clay paste in different container. The fine and coarse clay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…But the clays obtained from Ara will be applicable for the same purpose only upon blending. Saheed et al (2022) studied the suitability of Okelele clays for high-temperature applications. The RF and mechanical properties, like the compressive strength of the clay material, were studied, and the study showed that the compressive strength of these clay materials obtained from deposits in Nigeria was up to 7.7 kN.…”
Section: Introductionmentioning
confidence: 99%
“…But the clays obtained from Ara will be applicable for the same purpose only upon blending. Saheed et al (2022) studied the suitability of Okelele clays for high-temperature applications. The RF and mechanical properties, like the compressive strength of the clay material, were studied, and the study showed that the compressive strength of these clay materials obtained from deposits in Nigeria was up to 7.7 kN.…”
Section: Introductionmentioning
confidence: 99%
“…Other research [8][9][10][11] show that discarded shells may be used to make Portland cement, coarse aggregates, and concrete, among other building materials. For particular uses, other researchers have also experimented with various materials as composites [12][13][14]. Particleboard was originally created from wood, rice husks, sycamore leaves, citrus branches, beech twigs, and ordinary agricultural waste, according to the work mentioned [15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In the described work , radiation shielding materials were traditionally made from glass, rubber, polymer, elastomeric polymer, or vinyl binders with an elastic matrix packed with microscopic lead particles or lead oxide. Other applications for polymer composite materials have been reported [33][34]. Adsorption of catalysts in polyethylene manufacturing, hydrogen peroxide synthesis, as a selective adsorbent for numerous compounds including arsenic and fluoride, and sulfur removal from gas streams were only some of the applications for Al2O3 nanoparticles.…”
mentioning
confidence: 99%